Application of STEAM Project Based Learning Model to Improve Mathematical Creativity of Sixth Grade Students at SDN Binong, Pamarayan - Novia, Gita; Sopandi, Wahyu; Nurulpaik, Iik; Ulfah, Maria (International Conference on Elementary Education, 2025)
Mathematics learning in elementary schools is often still oriented towards final results and calculation skills alone, rather than the creative thinking process of students. Phenomena in the field show that most students experience difficulties when faced with contextual problems that require flexible and innovative thinking. This indicates that procedural learning has not been able to foster creativity and mathematical imagination. To address this challenge, this study aims to examine the effectiveness of project-based STEAM learning in improving the mathematical creativity of sixth-grade students at SDN Binong Elementary School in Pamarayan District. The study uses a quantitative approach with a one group pretest-posttest design, involving 28 students. The instruments used are mathematical creativity tests and learning activity observation sheets. The results of the analysis using a paired t-test showed a significant increase in students' mathematical creativity, with a pretest average score of 60.7 and a posttest average score of 84.2 (t = 9.03; p < 0.05). The most prominent improvement occurred in the aspects of originality and flexibility of thinking. These results indicate that project-based STEAM learning is able to transform the classroom into a space for exploring ideas, fostering the courage to innovate, and developing creative thinking skills in the context of real life.